Influência da BR - 174 na dinâmica da produção do espaço no Município de Rorainópolis-RR - Medeiros, Walliane da Costa Silva (2021)
The present dissertation aims to analyze the influence of the BR-174 highway on the production dynamics of space of the municipality of Rorainópolis. This research is justified from the need to discuss a little-observed topic, as well as, by proposing a reflection of social relations, built from the interaction between that municipality and the highway. This study is anchored in geography in interface with history. As methodological procedure were used, literature reviews, field studies and interviews with pioneer residents, relatives or people who had information or records for the research. In its structure, it initially presents a theoretical study on the analysis of space production, including central discussions and concepts. Then, it approach a survey of Amazon occupation policies, road and colonization projects implemented in the second half of the 20th century, as well as their socio-environmental applications and repercussions. Likewise, it also discusses the Roraima scenario in this context, from the creation of the municipality of Boa Vista-RR until the constitution of all other municipalities of Roraima. For the presentation of the research results (focusing on the period 1975-1995), the last chapter of this dissertation contextualizes the history of the municipality of Rorainópolis, the study of the genesis of the city's urban formation, the presence of the highway and its influence on the production of territorial space. After these surveys, the final considerations are presented, highlighting notes and evidence of the influence of BR-174 on the production dynamics of space of Rorainópolis- RR.